Reductionism (New Jersey : Everest Production, 2008)
Can we understand ourselves and the world in which we live by reducing and explaining it purely in terms of its parts or components? Or is it true that whole is greater than its parts. In this episode we will investigate reductionism as a scientific technique and as a worldview.
Executive producer, Nasuhi Yurt.
MaryLynn Schiavi.
Keywords: Reductionism